The relationship between political instability and economic growth in advanced economies: Empirical evidence from a panel VAR and a dynamic panel FE-IV analysis - Maximilian Dirks; Torsten Schmidt (RWI - Leibniz-Institut für Wirtschaftsforschung, 2023)
This paper analyzes the relationship between political instability and economic growth in advanced economies. Using a panel of 34 advanced economies from 1996 to 2020, we first employ a panel VAR estimated via System GMM, which allows us to explore the endogenous relationship between economic growth and political instability and to identify potential transmission channels. Second, we use an instrumental variable approach that exploits variation in median temperature and spillover effects of political instability from culturally approximate countries to establish causality. The empirical results suggest that political instability reduces GDP by 4 to 7 % five years after the shock, mainly through lower investment and consumption. A one standard deviation increase in economic growth reduces political instability by half a standard deviation, five years after the shock. – – In diesem Aufsatz analysieren wir die Beziehung zwischen politischer Instabilität und Wirtschaftswachstum für fortgeschrittene Volkswirtschaften sowie die potenziellen Wirkungskanäle zwischen beiden Größen. Dafür schätzen wir ein Panel-VAR mit Daten für 45 Volkswirtschaften von 1996 bis 2020. Zusätzlich verwenden wir einen Instrumentenvariablen-Ansatz, der Variationen in der Mediantemperatur und Spillover-Effekte politischer Instabilität aus kulturell ähnlichen Ländern nutzt, um kausale Beziehungen zwischen politischer Instabilität und Wirtschaftswachstum zu identifizieren. Die empirischen Ergebnisse deuten darauf hin, dass ein Schock der politischen Instabilität das BIP vor allem durch Anpassungsprozesse im Investitions- und Konsumverhalten um 4 bis 7 % verringert. Steigt hingegen das Wirtschaftswachstum, verringert dies die politische Instabilität fünf Jahre nach dem Schock um eine halbe Standardabweichung.
Keywords: C33; C26; O43; P16; 330; Political instability; economic growth; panel VAR; system GMM; Panel IV; local projection